Famous firsts in sports - Jakes, John, 1932- (Putnam's famous firsts series, 1967)
Describes thirty-six famous and obscure events and people making milestones in the history of sport. Includes the first: to hit sixty homers in a season, to vault fifteen feet, to climb Mt. Everest, to beat the four-minute mile, and to swim the English Channel.